Microsoft Dynamics 365 and the Power Platform. - von Courter, Gini (linkedin.com, 2019)
Learn how to leverage the Microsoft Power Platform—which is comprised of Microsoft Flow, Power BI, and PowerApps—with the cloud-based functions of Dynamics 365.